Energy Utilization Analysis and Flow Simulation for the Projected Al-Faizin Mosque’s Air Conditioning System - Khamis, Muhammad Nizam; Azlan, Mohd Azwir (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The project emphasizes the significance of ensuring thermal comfort in mosques, focusing on Al-Faizin mosque. It addresses how inadequate thermal conditions can impact worship and emotional factors. The project analyzes air conditioning energy use by studying internal factors, structure, and existing systems in other mosques. It aims to optimize the mosque’s air conditioning system to provide suitable conditions while minimizing energy consumption. Methodologically, the project assesses Al-Faizin mosque’s layout and structure, determining a requirement of 45 horsepower across 13 air conditioning units with specific configurations for optimal cooling. Flow simulations indicate that units placed at 3 meters height achieve peak efficiency, maintaining temperatures between 22°C to 25°C during key times like Friday prayers, aligning with comfort standards of 22.5°C to 26°C. However, the study notes a 150% increase in electricity consumption post-installation, highlighting the need for energy-efficient models, regular maintenance, and moderate temperature settings (24-26°C). Recommendations include enhancing building insulation and utilizing HVLS fans for additional cooling. In conclusion, the project underscores that strategic use of energy efficient technologies can effectively balance thermal comfort with energy conservation goals in mosque settings like Al-Faizin mosque.